Model Bimbingan dan Konseling Untuk Generasi Z dalam Menghadapi Era Revolusi Industri 4.0: Guidance and Counseling Model for Generation Z in Facing the Industrial Revolution 4.0 Era - Nur Madani Fitri; Aswar, Aswar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2024)
The era of the industrial revolution 4.0 requires humans to be able to adapt to technology and machine automation. With technology, all human activities can be carried out easily. This is what Generation Z is now facing, where they are known as digital natives who are used to technology. Generation Z is known as a generation that lives side by side and cannot be separated from technology. Therefore, the education process, including the provision of guidance and counseling services, must also be adapted to the characteristics of Generation Z, which cannot be separated from technology. The method used in this research is the content analysis. The conclusion of this research is that in providing services to generation z in this era, the BK service method that can be used is the online counseling or cybercounseling method.